Disruption of Modern Subjectivity as a History of Postmodern Objectivity: Exploring the Evolution of Subjectivity in Postmodernism (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Postmodernism brings immediately to mind the ideas of fracturing, fragmentation, indeterminacy and plurality. For Hassan it is the ideas of new aesthetic formation. Lyotard and Harvey defined it is a conditioning. For Connor it is the part of culture. It is a set of artistic movement employing a parodical mode of self-conscious representation for Hutchinson. Postmodernism is an illusion for Terry Eagleton. Whatever the definition is the subjectivity of postmodernity rooted in several ideas that is not regarded as typical postmodern. Prior to Descartes human subject tended to be conceived as the product of external forces and plans (Devine). But these ideas are replaced by his concept of subjectivity. Immanuel kant also describe a shared structure of subjective consciousness which are condition of possibility od objective knowledge. Freud and Lacan also tried to describe unconsciousness is the supplement of conscious mind. According to Fanon self-centered and self-certain universal subjectivity is impossible. It is generated through the interaction with others. Helene Cixous explained feministic subjectivity trough the essay Stories Out and Out.Objectives – The paper is an attempt to study history of ideas on subjectivity in postmodernism. This paper deals with some theories from its origin as these paved the way to its own postmodern shape.